2023
DOI: 10.3390/met13101706
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Homogenisation Parameters on the Microstructure and Hardness of AlMnFeMgSi(Zr) Wrought Alloys

Jette Broer,
Sina Mallow,
Kevin Oldenburg
et al.

Abstract: The purpose of this investigation is to improve the mechanical properties of AlMnFeMgSi wrought alloys by forming a high number density of nano-scaled strengthening dispersoids during homogenisation annealing. The process chain for AlMnFeMgSi wrought alloys includes homogenisation annealing after continuous casting. In this step, inhomogeneities and segregations are dissolved and dispersoids are precipitated. The formed dispersoids hinder grain growth, but usually cannot increase the strength due to their coar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The TEM examinations were performed on a JEOL-2100 microscope (JEOL Ltd., Tokyo, Japan) operating at 200 kV. The TEM foils were prepared following the standard electro-polishing techniques for Al alloys [16,17]. Cross-sectional TEM examinations were carried out to measure average grain size (d) of the hot-deformed alloys using a linear intercept method, for which at least 150 grains were examined to obtain an average value.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TEM examinations were performed on a JEOL-2100 microscope (JEOL Ltd., Tokyo, Japan) operating at 200 kV. The TEM foils were prepared following the standard electro-polishing techniques for Al alloys [16,17]. Cross-sectional TEM examinations were carried out to measure average grain size (d) of the hot-deformed alloys using a linear intercept method, for which at least 150 grains were examined to obtain an average value.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, at least 200 precipitates were measured to determine the average inter-particle spacing. More details about the measurements of precipitates are provided in previous publications [16,17,20]. Image analysis was performed by geometrical phase analysis (GPA) [21], where the reference area used in the digital processing as a strain-free area was chosen in the matrix as far as possible from the precipitate under study, as a general procedure.…”
Section: Methodsmentioning
confidence: 99%
“…On the one hand, good mechanical and sagging resistance properties could be obtained through the optimization of the processing technology. Broer [4] revealed that the mechanical properties resulting from homogenization at lower temperatures could show an increase of approximately 40% compared to the reference homogenization at 550 • C. Kang [9] studied the effects of annealing and deformation on the sagging resistance of 4433/3003/6111/3003 clad sheet, and the results show that low-temperature annealing and a small amount of coarse recrystallized grains could suppress the erosion of Si, resulting in better sagging resistance and strength. On the other hand, alloying to produce dispersed and high-temperature-resistant fine particles is also an effective method to improve high-temperature strengths [11][12][13]26].…”
Section: The Influence Of Alloying On the Mechanical Properties Of Al...mentioning
confidence: 99%
“…Fin materials usually include a steel strip, a copper strip, and an aluminum strip. Due to its characteristics of light weight, suitable strength, good corrosion resistance, thermal conductivity, brazing and processing formability, 3××× series aluminum alloy has become the main fin material for heat exchangers [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%